Extending the JD-R Framework: The Mediating Role of Work-School Conflict and Job Satisfaction on Employee Performance - Nurhayati, Mafizatun (Universitas Negeri Semarang, 2025)
The growing number of individuals simultaneously pursuing full-time work and formal education presents significant dual-role challenges that impact job performance and psychological well-being. This study explores how high workload influences employee performance, with work-school conflict and job satisfaction as mediators. Drawing on Job Demands–Resources (JD-R) Theory and Role Stress Theory, the research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) on data collected from 312 working students in Jakarta. Findings reveal that job satisfaction significantly enhances employee performance, whereas workschool conflict exerts a strong negative influence on both satisfaction and performance. While high workload directly improves performance indicating a potential challenge stressor effect it also increases work-school conflict, which in turn undermines job performance. However, job satisfaction does not significantly mediate the relationship between workload and performance, indicating that role strain, rather than positive affect, plays a more critical role in this dual-role context. The study highlights strain-based conflict as the dominant form of interference impacting productivity. Theoretically, it extends the JD-R framework by integrating dual-role conflict as a contextual mediator and refining the distinction between challenge and hindrance demands. Practically, the study encourages organizations to offer flexible workload arrangements and supportive leadership, while educational institutions are urged to provide adaptive academic systems to support dual-role learners.